Optimasi Prototipe Turbin Angin Menggunakan Metode Conjugate Gradient - Bilalodin, Bilalodin; Sugito, Sugito (BERKALA FISIKA, 2010)
One of the principal issue of energy conversion from wind energy to electrical energy is the optimization of its conversion process. Energy conversion is called optimum if the power lost is  minimum. The condition can be attained at the development stage of a wind turbine prototype.  This research will determine the optimum value the  variables of  various operation condition by using  multivariables Conjugate Gradient (CG) optimization algorithm. It is found that the optimum value is attained at  H = 1,0 m and D = 0,6 m, hence minimum power lost. The performance of turbine prototype design at laboratory, showed that the turbine can testing at low and high wind speed and   the irrespective of wind direction condition.    Keywords :  optimalization, prototype, wind turbin, conjugate gradient